Problems of formation of terminological system in hindi language (Journal of Oriental Studies, 2018)
A consistent and systematic study of changes in the development andformation of banking terms due to the need of time. Whereas the scope ofbanking terms is established, as in other industries, and the process of developmentis going on. This article investigated aspects of the emergenceand establishment of definitions of the banking terminology.